Zelfstandigheidspolitiek. De achtergrond van een cruciale term in het buitenlands beleid van Nederland 1900-1940 - Hertog, J. den (BMGN - Low Countries Historical Review, 2009)
The Policy of Independence. The Background of a Crucial Phrase in Dutch Foreign Policy 1900-1940The phrase ‘policy of independence’ was coined by the Dutch Minister of Foreign Affairs Van Karnebeek after the First World War. It has aroused a lot of discussion ever since. The phrase is often portrayed as sign of a change from a passive policy of neutrality to a much more active foreign policy. In this article the use of the phrase and the question of continuity or discontinuity are raised. This is done first of all on the basis of some crucial episodes from the First World War and subsequently the Dutch policy towards the German emperor and crown prince, Belgium and the League of Nations. This contribution argues that throughout those years the Dutch government pursued a policy characterized by activity and adopted an attitude that adhered to international law. Even before 1914 this approach was referred to as ‘independent’. Thereafter, Van Karnebeek coined the phrase ‘policy of independence’ to give expression to this prevailing attitude.